Teacher Educator Identity in a Culture of Iterative Teacher Education Program Design: A Collaborative Self-Study. Issue 2 (3rd May 2016) - Chang, Aurora; Rak Neugebauer, Sabina; Ellis, Aimee; Ensminger, David; Marie Ryan, Ann; Kennedy, Adam
Abstract: Faculty in the School of Education have collaborated to re-envision teacher education at our university. A complex, dynamic, time-consuming and sometimes painstaking process, redesigning a teacher education program from a traditional approach (i.e. where courses focus primarily on theoretical principles of practice through textbooks and university-based classroom discussions) to a model of teacher education that embraces teaching, learning and leading with schools and in communities is challenging, yet exciting work. Little is known about teacher educators' experiences as they either design or deliver collaborative field-based models of teacher education. In this article, we examine our experiences in the second implementation year of our redesigned teacher education program, Teaching, Learning, and Leading with Schools and Communities (TLLSC) and how these unique experiences inform our teacher educator identities. Through a collaborative self-study, we sought to make meaning of our transformation from a faculty delivering a traditional model to educators collectively implementing a field-based model, by analyzing the diverse perspectives of faculty at different entry points in the TLLSC development and implementation process. We found that our participation in an intensive field-based teacher preparation model challenged our notions of teacher educator identity. In a culture of iterative program design, this study documents the personal and professional shifts in identity required to accomplish this collaborative and dynamic change in approach to teacher education.